THEORETICAL AND METHODOLOGICAL BASIS INTRODUCTION OF SUGGESTIVE AND PEDAGOGICAL TECHNOLOGIES IN PROFESSIONAL TRAINING OF FUTURE MUSIC TEACHERS IN HIGHER EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2009)
Theoretic-methodic principles of introduction of suggestive-pedagogical technologies in professional preparation of future music masters in higher educational establishments. The problems of forming of new forms of consciousness are examined in the article, multidimensional thought of suggestive - pedagogical technologies facilities; uses of elements of musical therapy in professional preparation of future music masters for opening of individual possibilities of students, adjustment of the emotional states; implementation of tasks and use of methods of editing is offered, dialog, analysis, comparisons in an teaching educational process for the feasance of influence on students with the purpose of forming of musical presentations, development of fantasy.
Keywords: suggestive-pedagogical technologies; suggestive influence; future music master; musical therapy